Losing the moon - Henry, Patti Callahan (Berkley, an imprint of Penguin Random House LLC, 2020)
Like most mothers, Amy Reynolds has anticipated the moment when her son brings home his first serious girlfriend. But she's shocked to meet the girl's father. Nick Lowry was the college boyfriend who captivated her heart and sould and then, without a word of explanation or warning, disappeared. She still wonders what took him away from her. Amy's marriage is satisfying, her teenage children thriving. She loves her beautifully restored home and her work teaching at the local college. She has long since buried memories of Nick. But now that he is back in her life, she can't help recalling the beach where they pledged their destinies together twenty years ago. She can't help missing the young woman she was then, full of passion and promise. And she can't help being tempted by the life she might have lived ... might still live - even though making that choice would betray all she holds dear.